Providing a Metropolitan Perspective to Development Planning: Cagayan de Oro - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
Cagayan de Oro City (CDO), being the regional capital of Northern Mindanao and being linked with various port cities, extends its socioeconomic and political influence to its neighbors. The perceived emergence of metropolis with CDO as the core city has led to the conceptualization of the Metro CDO Special Development Project. Recently, MCSDP has been concentrating on infrastructure development linking CDO and Iligan City. Hence, by 1996, a comprehensive master planning for Metro CDO has been proposed to revise its focus on CDO and its immediate environment. This paper aims to discuss recent developments related to Metro CDO and highlights areas needing greater emphasis and further strengthening.
Keywords: 330; metropolitan structure; metropolitan planning and development